2021
DOI: 10.1111/ced.14520
|View full text |Cite
|
Sign up to set email alerts
|

Use of hydrochlorothiazide and risk of nonmelanoma skin cancer in Koreans: a retrospective cohort study using administrative healthcare data

Abstract: Background. The incidence of skin cancer is increasing because of the ageing population and ultraviolet exposure, and previous studies have revealed that long-term use of hydrochlorothiazide (HCTZ), an antihypertensive agent, has been associated with an increased risk of nonmelanoma skin cancer (NMSC). However, the association of NMSC and HCTZ within East Asian populations is unclear. Aim. To investigate the risk of NMSC in Korean subjects using HCTZ. Methods. A retrospective cohort study was conducted using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 24 publications
1
0
0
Order By: Relevance
“…After the inclusions of one duplicated case–control study on hydrochlorothiazide and indapamide in Denmark [ 42 ] and one duplicated cohort study in Korea [ 48 ], the results were consistent with those of the main analyses (Additional file 1 : Table S8). In addition, the sensitivity analysis including only low risk-of-bias studies showed consistent results with those of the main analysis (Additional file 1 : Table S9).…”
Section: Resultssupporting
confidence: 75%
“…After the inclusions of one duplicated case–control study on hydrochlorothiazide and indapamide in Denmark [ 42 ] and one duplicated cohort study in Korea [ 48 ], the results were consistent with those of the main analyses (Additional file 1 : Table S8). In addition, the sensitivity analysis including only low risk-of-bias studies showed consistent results with those of the main analysis (Additional file 1 : Table S9).…”
Section: Resultssupporting
confidence: 75%